Outcome of Four Layered Bandaging in Venous Leg Ulcer due to Varicose Veins - Karmacharya, Robin Man; Vaidya, Satish; Yadav, Binay; Kunwar, Kajol; Pote, Sneha; Manandhar, Anu; Bhandari, Niroj; Bhatt, Swechha (Annapurna Journal of Health Sciences, 2026)
Introduction: Venous ulcer is the late sequele of venous diseases like varicose veins, deep vein thrombosis. Four layered bandaging (4LB) is a multicomponent elastic bandaging technique used for the treatment of venous ulcer. However, the efficacy of this treatment in our context hasn’t been well studied. The main aim of this study was to know the outcome of 4LB bandaging in venous ulcer due to varicose veins in patients presenting to university hospital of Nepal.Methods: This cross-sectional study included patients with venous ulcers secondary to varicose veins presenting to the Vascular Unit outpatient department at Dhulikhel Hospital from January 1, 2021, to October 31, 2022. All eligible patients were treated with four-layer bandaging (4LB).Patients with concomitant arterial disease (ankle–brachial index